Evaluating the effects of dark chocolate formulated with micro‐encapsulated fermented garlic extract on cardio‐metabolic indices in hypertensive patients: A crossover, triple‐blind placebo‐controlled randomized clinical trial. (9th March 2022) - Mohammadi, Salman; Mazloomi, Seyed Mohammad; Niakousari, Mehrdad; Ghaem Far, Zohreh; Azadi, Amir; Yousefinejad, Saeed; Jafari, Peyman; Faghih, Shiva
Abstract: This study aimed to investigate the health‐related effects of microencapsulated fermented garlic extract (FGE) containing dark chocolate in hypertensive adults. For this purpose, 36 hypertensive adults (15 males vs. 21 females) were randomized to receive the FGE (5 g/day) dark chocolate containing 650 mg of FGE powder or the placebo. Intervention periods lasted for 6 weeks and were separated by a 3‐week wash‐out period. The response variables included blood pressure, anthropometric indices, lipid profile, and inflammatory and oxidative stress indices. Statistical analyses were performed using the Pkcross procedure, and Cohen's d was estimated for all response variables. There was no significant inter‐period difference between the mean changes of body weight, waist circumference, and body mass index (BMI). Furthermore, no significant change was confirmed in participants' blood pressure, triglycerides, total cholesterol, low‐density lipoprotein (LDL), high‐density lipoprotein (HDL), very low‐density lipoprotein (VLDL), serum homocysteine, high‐sensitive c‐reactive protein (hs‐CRP), malondialdehyde (MDA), and total antioxidant capacity (TAC). It seems that the dose of FGE used in this study was not sufficient to cause any significant changes in the outcomes. Therefore, further studies with dose–response designs and longer durations are recommended.